Frequency and molecular basis of CD36 deficiency among platelet donors in Kunming, China. (31st December 2023) - Lyu, Qilu; Peng, Mozhen; Chen, Qiang; Ji, Xin; Wang, Zhijiang; Li, Qian; Zhang, Zhihui; Luo, Zhen; Yin, Yonghua; Su, Pincan; Santoso, Sentot; Wang, Jue
Abstract: CD36 is a multifunctional receptor expressed on the surface of many cell types. Among healthy individuals, CD36 may be absent on platelets and monocytes (type I deficiency) or platelets alone (type II deficiency). However, the exact molecular mechanisms underlying CD36 deficiency remain unclear. In this study, we aimed to identify individuals with CD36 deficiency and investigate the molecular basis underlying it. Blood samples were collected from platelet donors at Kunming Blood Center. Platelets and monocytes were isolated and CD36-expression levels were analyzed using flow cytometry. DNA from whole blood and mRNA isolated from monocytes and platelets of individuals with CD36 deficiency were analyzed using polymerase chain reaction (PCR) testing. The PCR products were cloned and sequenced. Among the 418 blood donors, 7 (1.68%) were CD36 deficient: 1 (0.24%) with type I deficiency and 6(1.44%) with type II deficiency. Six heterozygous mutations occurred, including c.268C>T (in type I individuals), c.120 + 1 G>T, c.268C>T, c.329_330 del /AC, c.1156 C>T, c.1163A>C, and c.1228_1239 del /ATTGTGCCTATT (in type II individuals). Mutations were not detected in one type II individual . At the cDNA level, only mutant, but not wild-type, transcripts were detected in the platelets and monocytes of type I individual. In type II individuals, only mutant transcripts were found in platelets, whereas monocytes possessed wild-type and mutant transcripts. Interestingly, only alternative splicing transcripts were observed in the individual without mutation. We report the incidence rates of type I and II CD36 deficiencies among platelet donors in Kunming. Molecular genetic analyses of DNA and cDNA demonstrated that homozygous mutations on the cDNA level in platelets and monocytes or platelets alone identified type I and II deficiencies, respectively. Furthermore, alternatively spliced products also potentially contribute to the mechanism of CD36 deficiency. Plain Language Summary: What is the context? Healthy individuals may lack CD36 on platelets and (or) monocytes, which are defined as Type I and Type II CD36 deficiency. These individuals could develop anti-CD36 antibodies associated with immune-mediated disorders. However, the mechanism underlying the CD36 deficiency is still unclear. In this study, we reported the incidence of CD36 deficiency in Kunming platelet donors and found the new molecular basis of CD36 deficiency individuals. What's new? Molecular genetic analysis of cDNA derived from type I subjects showed the presence of mutant transcript only, both in platelets and monocytes. In type II subjects, platelets only carry mutant transcript, whereas monocytes possessed both wild-type and mutant transcripts. Furthermore, we found that alternatively spliced product of CD36 transcript could also contribute to the mechanism of CD36 deficiencies. What's the impact? Our finding indicates that analysis of CD36 at cDNA level is mandatory to verify different forms of CD36 deficiencies. This information may help us to understand the development of anti-CD36 antibodies in CD36 deficient individuals